Investigation of functionalized carbon nanotubes' performance on carbon dioxide hydrate formation. (1st May 2019) - Nashed, Omar; Partoon, Behzad; Lal, Bhajan; Sabil, Khalik M.; Shariff, Azmi Mohd
Abstract: In this work, the impact of functional group on the thermodynamics and kinetics of CO2 hydrates are investigated experimentally. The hydroxylated multi-wall carbon nanotubes (OH-MWCNT) and carboxylated carbon nanotubes (COOH-MWCNT) along with pristine carbon nanotubes (MWCNT) are selected for this study. The carbon nanotubes are suspended in a 0.03 wt% sodium dodecyl sulfate (SDS) aqueous solution and the results are compared with SDS aqueous solution at the same concentration of 0.03 wt% and deionized water. The CO2 hydrate phase boundary and kinetic parameters of CO2 hydrate formation including induction time, the initial rate and amount of gas consumed, gas uptake, storage capacity, and water to hydrates conversion are studied. The results show that the nanofluids studied do not affect the equilibrium conditions of CO2 hydrates. In addition, 0.01 and 0.05 wt% of COOH-MWCNT mixed with 0.03 wt% SDS showed highest initial hydrate formation rate and gas uptake. Furthermore, a comparison between SDS and COOH-MWCNT (without stabilizer SDS) at 0.03 wt% revealed that addition of COOH-MWCNT to the water enhance the initial hydrates formation rate compared to SDS. Highlights: Carbon nanotube does not change CO2 phase equilibrium. The kinetic of CO2 hydrates formation in the presence of SDS and carbon nanotube are discussed. Nanofluid contain 0.05 wt% COOH-MWCNT+0.03 wt% SDS is the most efficient promoter. Surfactant-free of COOH-MWCNT nanofluid show higher initial CO2 hydrate formation rate compared to SDS. Amount of gas consumption, storage capacity, and water to hydrates conversion rate are discussed.